GUILLAIN-BARRÃ‰ SYNDROME - Gyang Hanandita Gusti Putri; Nectarine Natasya Regitta Yasmin; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2023)
Guillain-BarrÃ© Syndrome (GBS) is an infection-preceded autoimmune disease attacking myelin sheath of neurons through molecular mimicry, causing neuron demyelination and conduction disruption. GBS is classified into four subtypes: Acute Inflammatory Demyelinating (AIDP), Acute Motor Axonal Neuropathy (AMAN), Acute Motor Sensory Axonal Neuropathy (AMSAN), and Miller Fisher Syndrome. It affects spinal radix which resulted in polyneuropathy, showing mainly symptoms of ascending paresis of the extremity and areflexia. Cerebrospinal fluid evaluation is essential to distinguish GBS from its vast differential diagnosis, with main finding of albuminocytologic dissociation. GBS needs to be managed as fast as possible with intravenous immunoglobulin administration or fresh frozen plasma exchange due to its fast progression.